Behind the façade of Stalin's command economy : evidence from the Soviet state and party archives - Gregory, Paul R. (Hoover Institution Press publication, 2001)
"The opening of the once secret Soviet state and party archives in the early 1990s was an event of profound significance. Western scholars gained access to the same documents as had Soviet leaders, penetrating the official wall of secrecy that had stood firm for decades. But while considerable archive-based research on that period has been published over the past five years, relatively little work has been devoted to the economics of the Stalin system. Although the Stalinist command economy is supposedly a thing of the past, it continues to plague Russia's transition to a market economy, and, more important, it continues to have considerable emotional appeal as a substitute for a market economy." "Examining the period from the early 1930s through Stalin's death in 1953 - the period of the creation of the Stalinist system - this book reveals what we have learned from the archives, what has surprised us, and what has confirmed what we already knew."--Jacket